Great muslim physician and islamic jurist: A portrait of Ibn Al-Nafis - Ishak, Mohd. Shuhaimi; Solihin, Sohirin Mohammad (Kulliyyah of Science, IIUM, 2012)
The research aims at revealing the contribution and scholarly work of Ibn al-Nafis in the field of medicine and Islamic jurisprudence. It sheds light on the views of his contemporaries related to his theoretical framework of the two aspects of disciplines. Moreover, it discloses his historical background and his extensive study on medicine. As he was a man of ideas and also a prolific writer, the study also traces the opinions of others on him. The study also focuses on exposing the validity of his medical theory as well as Islamic jurisprudential views, which became the source of admiration by his contemporaries.